2020
DOI: 10.3389/fcimb.2020.00073
|View full text |Cite
|
Sign up to set email alerts
|

Household Pet Ownership and the Microbial Diversity of the Human Gut Microbiota

Abstract: The human gut microbiome has a great deal of interpersonal variation due to both endogenous and exogenous factors, like household pet exposure. To examine the relationship between having a pet in the home and the composition and diversity of the adult gut microbiome, we conducted a case-control study nested in a larger, statewide study, the Survey of the Health of Wisconsin. Stool samples were collected from 332 participants from unique households and analyzed using 16S rRNA sequencing on the Illumina MiSeq. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Dog owners have been found to share skin microbiota with their pets, and ownership of household pets including dogs and cats has been suggested to be associated with differences in the gut flora of the owner. 45 46 A recent study also reported a large influence of diet on the gut microbiota of dogs. 47 It is thus possible that shared microbial communities could influence both owner and dog health, and also that shared dietary and physical activity patterns could affect gut microbiota in dog owners and their pets in a similar fashion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Dog owners have been found to share skin microbiota with their pets, and ownership of household pets including dogs and cats has been suggested to be associated with differences in the gut flora of the owner. 45 46 A recent study also reported a large influence of diet on the gut microbiota of dogs. 47 It is thus possible that shared microbial communities could influence both owner and dog health, and also that shared dietary and physical activity patterns could affect gut microbiota in dog owners and their pets in a similar fashion.…”
Section: Discussionmentioning
confidence: 96%
“…A potential partial explanation for our findings could be shared microbiota influencing diabetes risk in both owners and their pets. Dog owners have been found to share skin microbiota with their pets, and ownership of household pets including dogs and cats has been suggested to be associated with differences in the gut flora of the owner 4546. A recent study also reported a large influence of diet on the gut microbiota of dogs 47.…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic has increased alcohol consumption and smoking habits ( 38 ), in populations—both known to modulate the oral, lung, and gut microbiota ( 39 , 40 ). A more unexpected result of the pandemic is the increase in pet ownership, which in itself can impact on the human gut microbiome ( 41 ).…”
Section: Indirect Effects Of Pandemic On An Individual or Populationsmentioning
confidence: 99%
“…The pandemic has also been reported to alter sleeping patterns and quality ( 44 ), which in turn can negatively affect mood, stress, and anxiety. Additionally, the circadian rhythm is known to have a bidirectional relationship with the gut microbiome—disturbances in the gut microbiome can affect sleep regulation ( 41 ), and disturbances in circadian rhythms can alter the gut microbiome ( 45 ). This relationship has in fact been proposed as the mechanistic link between sleep disruption and metabolic syndrome, which can lead to diabetes, cardiovascular disease, and cancer ( 45 ).…”
Section: Indirect Effects Of Pandemic On An Individual or Populationsmentioning
confidence: 99%
“… 13 14 The Wisconsin Microbiome Ancillary Study in children and adults demonstrated the role of xenobiotics and other settings in shaping the human gut microbiome and increased risk for MDRO colonization. 53 – 55 This represents an important and novel area for metabolic, aging and population health research.…”
Section: Introductionmentioning
confidence: 99%